Application of Project Based Learning to Improve Learning Outcomes in Class IV Object Change Material at SDN 1 Cikunir - Asiah Jamil, Ai Nur; Nurkholis, Nurkholis; Lia Marliani, Neneng (Annpublisher, 2024)
This research is based on the problem of students not yet mastering the material on Changes in Form of Objects. This research aims to improve science learning outcomes regarding changes in the shape of objects through the Project-based Learning learning model for class IV students at SDN Cikunir 1. The type of research used is collaborative classroom action research; the subjects in this research are class IV students, with a total of 24 students. This research consists of four stages: planning, action, observation, and reflection. Data collection techniques are carried out by observation and tests. Data collection tools use observation sheets and written test questions. The data analysis technique was carried out quantitatively and descriptively, and the nature of the research was collaborative. As for the difference in the average score of student learning outcomes in cycles I and II, it shows an increase in the ability of students' learning outcomes with the Project Based Learning learning model, as shown by the increasing evaluation results in each cycle. In cycle I, the average was 54%; in cycle II, the average learning outcomes were obtained at 82%. Therefore, applying the project-based learning model can improve student learning outcomes in Class IV Changes in Form material at SDN 1 Cikunir.